KNOWLEDGE MEASUREMENT SYSTEM (KMS) - MIHO, WALEED SHABAN (Fırat Üniveristesi, 2020)
In this age of information and great advancements in every area of knowledge, technology has become a crucial part of everyday human life. One of the most important areas for our future surly is Information and Communication Technology (ICT). However, the current systems are not sufficient enough to measure the level of the student with accuracy. This system is not only just giving courses, lessons, and exams, but the levels of students are calculated and evaluated very accurately. In addition to taking advantage of the discussions that could be shared on it, whether between the students themselves, where they can publish topics as well or between the teacher and students, where he can put topics for discussion and interaction. Other than that, it is easy to use and there are no unnecessary complications and increases. As in this system that can almost perfectly track the activities and the abilities of every student in his/her during the academic years. In this study, we attempt to further ahead of the goal of reaching a highly accurate grading system. The proposed system has been designed and implemented using the tools: (MySQL, HTML, CSS, PHP, JavaScript, JQuery, Ajax, and Bootstrap). The students and staff of the selected institutions participated in the implementation. The results have been obtained and evaluated using student measurement.

Bu bilgi çağında ve bilginin her alanındaki büyük ilerlemelerde, teknoloji günlük insan yaşamının önemli bir parçası haline gelmiştir. Gelecekteki somurtkanımız için en önemli alanlardan biri Bilgi ve İletişim Teknolojisidir (ICT). Ancak, mevcut sistemler öğrencinin seviyesini doğru bir şekilde ölçmek için yeterli değildir. Bu sistem sadece dersler ve sınavlar vermekle kalmıyor, aynı zamanda öğrencilerin seviyeleri de çok doğru bir şekilde hesaplanıyor ve değerlendiriliyor. Üzerinde paylaşılabilecek tartışmalardan yararlanmanın yanı sıra, ister öğrencilerin kendileri arasında, hem de konuları yayınlayabilecekleri ya da öğretmen ve öğrenciler arasında, tartışma ve etkileşim için konu koyabileceği konular. Bunun dışında kullanımı kolaydır ve gereksiz komplikasyonlar ve artışlar yoktur. Bu sistemde olduğu gibi, akademik yıllarda her öğrencinin faaliyetlerini ve yeteneklerini mükemmel bir şekilde izleyebilir. Bu çalışmada, son derece hassas bir derecelendirme sistemine ulaşma hedefinin ötesine geçmeye çalışıyoruz. Önerilen sistem şu araçlar kullanılarak tasarlanmış ve uygulanmıştır: (MySQL, HTML, CSS, PHP, JavaScript, JQuery, Ajax ve Bootstrap). Seçilen kurumların öğrencileri ve personeli uygulamaya katılmıştır. Sonuçlar öğrenci ölçümü kullanılarak elde edilmiş ve değerlendirilmiştir.
Bilgi ölçüm sistemi
Keywords: Bilgisayar Mühendisliği Bilimleri-Bilgisayar ve Kontrol